2012
DOI: 10.1371/journal.pone.0048866
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell-Directed Vaccination with a Lentivector Encoding PSCA for Prostate Cancer in Mice

Abstract: Many studies have demonstrated that prostate stem cell antigen (PSCA) is an attractive target for immunotherapy based on its overexpression in prostate tumor tissue, especially in some metastatic tissues. In this study, we evaluated dendritic cell (DC)-directed lentiviral vector (DCLV) encoding murine PSCA (DCLV-PSCA) as a novel tumor vaccine for prostate cancer in mouse models. We showed that DCLV-PSCA could preferentially deliver the PSCA antigen gene to DC-SIGN-expressing 293T cells and bone marrow-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…It has been found that f.p. (footpad area) injections of LVs induced much higher responses than the intramuscular area injection, subcutaneous area injection, and intraperitoneal injection [49]. It is speculated that administering by the f.p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that f.p. (footpad area) injections of LVs induced much higher responses than the intramuscular area injection, subcutaneous area injection, and intraperitoneal injection [49]. It is speculated that administering by the f.p.…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that administering by the f.p. route provides LVs a better chance to encounter DCs [49]. Direct administration of lentiviral vectors encoding TAA gene induced more potent TAA-specific immune responses when compared with the DCs that were transduced with lentiviral vectors ex vivo [50].…”
Section: Discussionmentioning
confidence: 99%
“…[90][91][92] Many studies have used genes encoding specific prostate antigens to induce an immunoresponse directed against prostate cancer cells only. Xiao et al 94 used lentivirus to deliver PSCA to prostate cancer. They reported a significant increase in CD8 + and CD4 + T cells after injecting the drug into mice.…”
Section: Immunomodulatory Gene Therapymentioning
confidence: 99%
“…By pseudotyping a LV with this mutated Sindbis virus derived envelope glycoprotein, targeted infection of murine DCs after direct subcutaneous administration was achieved. Moreover, this elicited strong and therapeutic antigen specific immune responses [5,[103][104][105]. Besides genetic alterations, the viral surface can also be chemically engineered to alter the binding specificity.…”
Section: Cell Entry Basedmentioning
confidence: 99%